Work-Life Balance and Emotional Intelligence on Retention: Mediating Role of Job Engagement in Manufacturing Industry - Yusraf, Dandi; Ramadhani, Norman Hilmi; Siddiq, Dedi Muhammad; Wibowo, Sandi Nasrudin (Universitas Muhammadiyah Pontianak, 2025)
This study had the aim to analyze the effects that work-life balance as well as emotional intelligence have on employee retention, with a mediating variable which is job engagement, in manufacturing sector companies in Cirebon. Quantitative approach was used as the research method, with a survey through a questionnaire to 187 respondents. The data analyzed by using Statistical Package for the Social Sciences (SPSS). The findings revealed that work-life balance as well as emotional intelligence positively affect employee retention. Furthermore, job engagement is proven as a mediating variable that strengthens the effects of these two factors on employee retention. Thus, this study highlights how important is work-life balance along with emotional intelligence in improving employee engagement and loyalty, and provides implications for human resource management strategies in the manufacturing sector.